Pr/Ph ratio in the Bazhenov formation rock samples (Western Siberia); The 25th International Meeting on Organic Geochemistry, Interlaken, Switzerland, 18-23 september 2011 - Goncharov I. V. Ivan Vasilyevich; Samoylenko V. Vadim; Oblasov N. Nikolay; Volkov V. Vladimir (2011, 2011)
В фонде НТБ ТПУ отсутствует